2009
DOI: 10.1074/jbc.m109.007583
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Processing of HCN2 and Co-assembly with HCN4 in the Generation of Cardiac Pacemaker Channels

Abstract: In sino-atrial and atrio-ventricular nodal cells, hyperpolarization-activated cyclic nucleotide-gated (HCN) inward current carrying cationic channels, I f , are expressed that contribute importantly to the diastolic depolarization critical for cardiac pacemaker activity. Although previous studies have demonstrated myocardial expression of both the HCN2 and HCN4 subunits, the specific roles of these subunits in the generation of functional myocardial I f channels remain unclear. To explore the molecular composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…In the presence of PNGaseF, the HCN2 band is completely shifted to ϳ90 kDa, suggesting that cardiac HCN2 channels are fully N-glycosylated in vivo. These molecular masses are consistent with a nonproteolyzed form of HCN2, as has been reported for rat and human ventricles (17,36,46,57,59).…”
Section: Hcn2 Channels Undergo N-glycosylation In Native Cardiacsupporting
confidence: 65%
“…In the presence of PNGaseF, the HCN2 band is completely shifted to ϳ90 kDa, suggesting that cardiac HCN2 channels are fully N-glycosylated in vivo. These molecular masses are consistent with a nonproteolyzed form of HCN2, as has been reported for rat and human ventricles (17,36,46,57,59).…”
Section: Hcn2 Channels Undergo N-glycosylation In Native Cardiacsupporting
confidence: 65%
“…Insufficiency of Simple Autoinhibition Model Based on V 1/2 Assessment Consequences for HCN channel modulation from truncations of the C-terminal region are likely to have physiological relevance, since C-terminal truncations have been identified in human patients with cardiac sinus node defects (Schulze-Bahr et al 2003;Schweizer et al 2010) and even in myocardial tissues of healthy mice (Ye and Nerbonne 2009). Thus, it is essential to generate a cohesive biophysical theory of how the molecular structure can determine kinetic properties.…”
Section: Discussionmentioning
confidence: 99%
“…3) (22,28,41,45,67,69,71,80,84). Comparison of transcripts from all four hyperpolarization-activated cation channels showed that expression of HCN1 and HCN4 were highest, although there were significant levels of HCN2 and HCN3 (Fig.…”
Section: Resultsmentioning
confidence: 99%